Soybean mitogen-activated protein kinase GMK2 is activated with GMK1 in Bradyrhizobium-Soybean interactions - Im, Jong Hee; Son, Seungmin; Lee, Hyoungseok; Kim, Ho Bang; An, Chung Sun (Genes & genomics, 2014)
Biological nitrogen fixation in root nodules is the primary nitrogen source for plants. In leguminous plants, nodulation is initiated by the recognition of the nodulation (Nod) factor, the signaling molecule secreted by rhizobia. Our previous study showed that 47-kDa and 44-kDa MAPKs were activated in soybean treated with a genistein-induced culture filtrate (GCF) of Bradyrhizobium japonicum . We investigated the activity and regulation of the 47-kDa MAPK, GMK1; however, the 44-kDa MAPK was not extensively studied. Herein, we identified the 44-kDa MAPK as Glycine max MAP kinase 2 (GMK2) and showed that its transcription was activated by GCF. GMK1 and 44-kDa MAPK were activated by phosphatidic acid (PA) and GCF-mediated induction of GMK1 and GMK2 activities were reduced by treatment with PA generation inhibitors. The activity of GCF-activated GMK2, but not GMK1, was decreased by calcium signaling inhibitors. Our data indicate that GMK2 expression is regulated at the transcriptional level and that GMK2 activity is regulated by phosphatidic acid and calcium during soybean- Bradyrhizobium interactions.